Parent and peer influences on adolescent delinquent behavior and the mediating role of self-regulation - Banzon-Librojo, Lorelie Ann; Liane Pena Alampay (Diliman, Quezon City Psychological Association of the Philippines, 2010)
"This study examined the influence of parent and peer variables on delinquent behavior, and explored whether the relationships were mediated by adolescent self-regulation."
Keywords: Delinquent Behavior; Adolescence; Self-regulator.; Parenting